Maternal dietary iron intake during pregnancy has a potential effect on the neonate gut microbiota profile - Qi, Qi; Liu, Danmeng; Wang, Liang; Zhu, Yingze; Gebremedhin, Mitslal Abrha; Zhu, Zhonghai; Zeng, Lingxia (Frontiers in Nutrition, 2025)
IntroductionIron is an essential nutrient during pregnancy and may influence the early development of the neonatal gut microbiota. This study aimed to investigate the association between maternal dietary iron intake during pregnancy and the gut microbiota (GM) characteristics of both the mother and neonate in a well-characterized cohort.MethodsNinety-five mother-neonate dyads were included in this study. Mothers completed a food frequency questionnaire (FFQ) providing estimates of dietary iron intake during pregnancy, and participants were categorized into higher (≥ median) or lower (< median) groups of maternal dietary iron intake. Fecal samples were collected from mothers (third trimester) and from neonates, and assessed via 16S rRNA amplicon sequencing. Differences in diversity and abundance of GM were compared between groups.ResultsThere was no difference in profile or diversity in maternal samples however, neonatal samples indicated greater diversity of GM in infants of mothers with higher intakes of iron (Shannon p = 0.04; Simpson p = 0.01). After stratification by delivery mode, in the stratum of normal vaginal delivery (NVD), Simpson diversity remained higher in the infants’ GM of mothers with higher intakes of iron (p = 0.04). The relative abundance of the core genus Bifidobacterium in NVD and cesarean section (CS) neonates showed higher in the higher group than that in the lower group, as the difference was not statistically significant. Maternal dietary iron intake was significantly associated with the neonate GM composition with variation explained 10.24% (p = 0.007).ConclusionAdequate dietary iron intake during pregnancy may promote beneficial bacterial colonization and increase the biodiversity of the neonate GM.